A cross-sectional study on distinctive factors associated with conduct behaviors among children presenting with inattention-hyperactivity disorders in Indian context - Anindya Kumar Ray; Saikat Mitra (Archives of Mental Health)
Introduction: Conduct behaviors are frequently associated with disorders of inattention and hyperactivity. Many studies have been done in the Western population on predictors of those conduct behaviors among these children with inattention-hyperactivity. However, such studies are lacking in the Indian context. Thus, the current study examined the distinctive factors associated with conduct behaviors among children presenting with inattention-hyperactivity Disorders in the Indian setting. Materials and Methods: A cross-sectional study was done in a Medical College of Kolkata with two groups of children and adolescents each having 50 samples diagnosed as hyperkinetic conduct disorder (HKCD) and hyperkinetic disorder of attention and activity (HKD-AA) as per International Classification of Diseases-10th version. Comparison between the two groups was made with the abbreviated (10-item) Conners’ rating scale for parents (CPRS-HI) and a semi-structured socio-demographic pro forma to find out the distinctive factors associated with HKCD. Results: On comparison between the two groups, significant differences (P < 0.05) were found in items such as male sex, birth complications, inadequate social-skill development, paternal alcohol use disorders (AUD), and disturbed family ambience, which were significantly higher in HKCD. Among CPRS-HI items, impulsivity was the distinguishing feature of HKCD. However, the total severity scores of CPRS-HI were similar in both the groups. In our population, maternal substance abuse was not found, and mood and alcohol use disorders were more common than childhood externalizing disorders in the family history. Conclusion: Similar to the Western population, in our study male sex, birth complications, paternal-AUD, and disturbed family ambience are distinctively higher in conduct behaviors, but contrary to them, there is no maternal substance abuse, and severity of inattention-hyperactivity scores are similar in children with or without conduct behaviors.